Manual para la evaluación de tecnologías sanitarias, versión corta - Reyes, Nora (2022)
The objective of this article is to present the methodological guidelines established in the manual of Short Health Technology Assessment, which were developed by the Peruvian National Network of Health Technology Assessments. The purpose of the manual is to standardize the methodologies of development of Short Health Technology Assessments between institutions of health technology assessment. This manual seeks to contribute to evidence-informed decision-making to improve the population's access to safe and effective health technologies in Peru